Knowledge, Attitude and Practices of Health Workers regarding Medical Waste Management in Entebbe Regional Referral Hospital, Wakiso District. A Cross-sectional Study. - Hanisha Lwasa Nakawooma; Gordon Nimwesiga (Student's Journal of Health Research, 2022)
Background: The purpose of the study was to assess the knowledge, attitude, and practices of health workers regarding medical waste management in Entebbe Regional Referral Hospital, Wakiso District. Methodology:  The study adopted a cross-sectional study design with a simple random technique as a sampling technique. Data were collected from 50 respondents using a semi-structured questionnaire written in the English language as a data collection tool; later analyzed manually using a scientific calculator, corded and entered into a computer, and presented in tables and figures for easy presentations. Results: All the study participants had ever heard about medical waste management, (60%) were aware of the medical waste management rules and regulations followed in Uganda, (70%) knew 48 hours as the maximum storage period for medical wastes, and (90%) knew segregation, collection and storage transportation, treatment, and disposal as the steps involved in the management of wastes, (50%) knew yellow color code for infectious and (70%) knew gloves as the personal protective equipment used during medical waste management, (94%) of respondents agreed that it is necessary to follow wastes management rules and regulations all the time, (and 52%) were willing to report safety violations done by their fellow workmates regarding waste management and (62%) perceived segregation of hospital wastes to be time-consuming. (90%) of respondents were fully vaccinated for common pathogens. Conclusion: Satisfactory knowledge was associated with favorable attitudes of health workers regarding medical waste management . Recommendation: Entebbe regional referral hospital administration should allocate the tasks and responsibilities to focal persons to properly monitor the medical waste management based on guidelines since the study discovered that some health workers were not following color coding while disposing of medical wastes.